2018
DOI: 10.1093/pcp/pcy125
|View full text |Cite
|
Sign up to set email alerts
|

SAG12, a Major Cysteine Protease Involved in Nitrogen Allocation during Senescence for Seed Production in Arabidopsis thaliana

Abstract: SAG12 is the most widely used senescence-associated reference gene for characterizing leaf senescence, and the increase in SAG12 protein during leaf senescence is remarkable. However, the role of this cysteine protease in N remobilization and the leaf senescence process remains unclear. The role of SAG12 has been poorly investigated and the few reports dealing with this are somewhat controversial. Indeed, sag12 Arabidopsis mutants have not shown any phenotype, while OsSAG12-1 and OsSAG12-2 overexpression in ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 51 publications
4
64
0
1
Order By: Relevance
“…S7). The lack of phenotypic differences between the pp2a-b9g and pp2a-b9g sag12 mutants mirrors the findings of Otegui et al, (2005) and James et al, (2018), who reported knock-out mutants lacking SAG12 function displayed no discernible change in the progression of developmental leaf senescence.…”
Section: The Yellowing Phenotype In the Apex Of Aging Pp2a-b9g Leavessupporting
confidence: 76%
“…S7). The lack of phenotypic differences between the pp2a-b9g and pp2a-b9g sag12 mutants mirrors the findings of Otegui et al, (2005) and James et al, (2018), who reported knock-out mutants lacking SAG12 function displayed no discernible change in the progression of developmental leaf senescence.…”
Section: The Yellowing Phenotype In the Apex Of Aging Pp2a-b9g Leavessupporting
confidence: 76%
“…Otegui et al (2005) showed that a lack of SAG12 did not prevent the formation of senescence associated vacuoles (SAVs), nor was their proteolytic activity affected, suggesting that other cysteine proteases accumulated in SAVs in the senescent leaves of Arabidopsis thaliana (Otegui et al, 2005). More recently, James et al (2018) confirmed the absence of a leaf senescence phenotype in sag12 . The authors also showed that there was no difference in yield and seed N content between Col and sag12 when cultivated under optimal N nutrition, but there was lower seed N content and yield in sag12 when cultivated under limiting nitrogen conditions.…”
Section: Introductionmentioning
confidence: 70%
“…Arabidopsis thaliana Columbia (Col) and sag12 (SALK_124030) T-DNA mutants were used in this study. The KO-SAG12 SALK_124030 ( sag12 ) was chosen because it was the only germplasm which was available in ABRC stock and recently characterized for some study focused on protease activities (Pružinská et al, 2017; James et al, 2018). Seeds were stratified for 48 h in 0.1% agar (Select agar, Sigma, L’Isle d’Abeau Chesnes, France) at 4°C in the dark and then sown into Eppendorf tubes (0.5 ml) filled with 0.8% agar (w/v) that had their bottoms removed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that SAG12 knockout Arabidopsis plants did not exhibit any special phenotypic traits when grown under an optimal nitrogen supply. Thus, the gene is involved in Rubisco degradation during the leaf senescence associated with seed filling ( James et al., ). In this study, our results showed that the expression of CsSAG12 in the mature leaves was upregulated by more than 5‐fold (Fig.…”
Section: Discussionmentioning
confidence: 99%